1992
DOI: 10.2527/1992.703811x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of quality protein maize for starter and finisher swine

Abstract: Growth trials with starter (n = 120, 6.8 kg initially, 28 d of age, Exp. 1) and finisher (n = 70, 59 kg initially, Exp. 2) pigs were conducted to compare quality protein maize (QPM, .40% lysine) and normal corn (.31% lysine) in simple corn-based diets containing the same levels of soybean meal. In Exp. 1, pig performance was similar (P greater than .10) on all diets, regardless of the level of soybean meal, suggesting that QPM and normal corn have similar feeding value in lysine-adequate (.99 to 1.11%) diets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 0 publications
5
11
0
3
Order By: Relevance
“…The approximate composition of QPM was similar to that of normal maize, although QPM tended to have higher levels of crude protein, ether extract, crude fibre and gross energy. Similar observations have been made by Burgoon et al (1992), Ahenkora et al (1994) and Martinez et al (1996). The amino acid profiles show that of the five critical amino acids, QPM had higher levels of arginine (+25%), cystine (+35%), tryptophan (+33%) and lysine (+33%) than normal maize, while the level of methionine in QPM was 5% less than in normal maize.…”
Section: Resultssupporting
confidence: 73%
“…The approximate composition of QPM was similar to that of normal maize, although QPM tended to have higher levels of crude protein, ether extract, crude fibre and gross energy. Similar observations have been made by Burgoon et al (1992), Ahenkora et al (1994) and Martinez et al (1996). The amino acid profiles show that of the five critical amino acids, QPM had higher levels of arginine (+25%), cystine (+35%), tryptophan (+33%) and lysine (+33%) than normal maize, while the level of methionine in QPM was 5% less than in normal maize.…”
Section: Resultssupporting
confidence: 73%
“…The improvement in protein quality of corn can have considerable commercial impact on monogastric livestock and poultry (Johnson et al 2001). Swine feeding studies have shown that QPM diets were superior to regular feed corn diets in terms of weight gains (Sullivan et al 1989) and reductions in the requirement for soybean meal supplementation that is sometimes used to increase the lysine content of corn meal (Burgoon et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Vários estudos foram realizados a respeito do potencial nutricional dos milhos QPM [3,7,8,9,10,11,12,25,27]. Entretanto, até o momento nenhuma pesquisa foi realizada avaliando a influência dos milhos QPM nas características sensoriais de produtos alimentícios.…”
Section: Discussionunclassified